Accuracy of core needle biopsy compared to fine needle biopsy for the diagnosis of neoplasm in patients with suspected head and neck cancers: a systematic review protocol of diagnostic test accuracy. Issue 7 (8th July 2020) - Soumya; Whitehorn, Ashley; Ooi, Eng H.; Lockwood, Craig
ABSTRACT: Objective: The objective of this review is to determine the difference in diagnostic accuracy of core needle biopsy and fine needle aspiration for patients with a head and neck mass using surgical histopathology as a reference test. The risks and adverse events associated with each technique will also be compared. Introduction: Tissue diagnosis is critical in evaluation of head and neck lesions to guide management. Options for tissue biopsy include surgical biopsy, fine needle aspiration and core needle biopsy. Inclusion criteria: Studies that compare ultrasound-guided core needle biopsy and/or fine needle aspiration to investigate lumps in the thyroid, cervical lymph nodes, or salivary glands for malignancy in adult patients will be included. The comparator test will be definitive histology in form of surgical biopsy/excision. Methods: MEDLINE, Emcare, Embase, Web of Science and Cochrane Register of Diagnostic Accuracy Studies will be searched. Studies will be critically appraised by two independent reviewers for methodological quality, using the modified critical appraisal instrument QUADAS-2 and JBI SUMARI software. Two independent reviewers will extract data from papers included in the review using the standardized data extraction tool available in the JBI Reviewer's Manual. Systematic review registration number: PROSPERO CRD42020140005.